2018
DOI: 10.1155/2018/9014768
|View full text |Cite
|
Sign up to set email alerts
|

Support Needs of Patients with Cushing’s Disease and Cushing’s Syndrome: Results of a Survey Conducted in Germany and the USA

Abstract: Background Cushing's disease (CD) and Cushing's syndrome (CS) are chronic illnesses, characterized by symptoms of prolonged hypercortisolism, which often changes to hypocortisolism after successful treatment. In view of the high disease burden of CD/CS patients and long-term impaired quality of life, the present survey was conducted to gain information about subjective illness distress and patients' specific needs in terms of supportive measures beyond medical interventions. Patients and Methods Cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…The present survey confirmed that no specific symptom initiated a diagnosis, but rather a range of burdensome symptoms occurring with similar frequency to those reported in previous surveys ( 1 , 2 ), with the notable difference in that in a USA-German survey, cognitive and psychological symptoms were bothersome for 61% of US and 66% of German patients ( 13 ), whereas in the present survey 38% considered depression/mood problems burdensome. Such differences may be a result of different terms being used to describe depression or mood symptoms as well as cultural differences between populations.…”
Section: Discussionsupporting
confidence: 90%
“…The present survey confirmed that no specific symptom initiated a diagnosis, but rather a range of burdensome symptoms occurring with similar frequency to those reported in previous surveys ( 1 , 2 ), with the notable difference in that in a USA-German survey, cognitive and psychological symptoms were bothersome for 61% of US and 66% of German patients ( 13 ), whereas in the present survey 38% considered depression/mood problems burdensome. Such differences may be a result of different terms being used to describe depression or mood symptoms as well as cultural differences between populations.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding educational and support programs, most of the patients preferred internet-based programs (89.3% US, 75.4% Germany). However, cultural differences and specific needs may differ in different populations of patients with CS (105). In other chronic diseases programs that improve self-manegement (where the patient has a more active role) have lead to better health status and increased QoL (105).…”
Section: Hints To Improve Patient's Quality Of Lifementioning
confidence: 99%
“…However, cultural differences and specific needs may differ in different populations of patients with CS (105). In other chronic diseases programs that improve self-manegement (where the patient has a more active role) have lead to better health status and increased QoL (105). Consequently, it would be helpful to develop specific programs for patients with CD too.…”
Section: Hints To Improve Patient's Quality Of Lifementioning
confidence: 99%
“…Also, PSG assist members to feel empowered in a situation that may induce feelings of helplessness by seeing how others in similar situation coped and by helping others. A recent study identified cultural differences in support needs of patients, so it is important to assess cultural preferences of the patient when evaluating the best fit with a PSG (Kreitschmann-Andermahr et al, 2018). In addition, some PSG are focused on providing support and education for family members, caregivers, friends, of someone with a chronic medical condition.…”
mentioning
confidence: 99%